Pengaruh Persepsi Harga terhadap Keputusan Menginap di Villa Gunung Geulis Camp Area Bogor - Nurudin, Muhamad; Djunaid, Ika Suryono (LPPM Institut Nasional Laa Roiba Bogor, 2024)
Tourist accommodation is currently experiencing a growing demand from the public, leading to heightened competition among accommodation businesses. As a result, these businesses are required to continuously innovate by providing excellent services, facilities, and competitive pricing. Consequently, this study aimed to investigate how perceptions of price influenced decision-making at Villa Gunung Geulis Camp in the Bogor Area. The research examined four dimensions related to price perceptions: affordability, price compatibility with product quality, price compatibility with benefits, and price competitiveness. Quantitative methods were employed, and data were collected through questionnaires and interviews. The research sample was determined using Nonprobability Sampling with the Accidental Sampling technique. The validity of the data was assessed using the Pearson Product Moment formula, while the reliability was tested using the Alpha Cronbach technique. The analytical approach used in the study involved simple linear regression analysis, performed using the SPSS Version 25 application. The results of the data analysis demonstrated a significant and positive influence of Variable X Price Perception on the decision to stay at Villa Gunung Geulis Camp in the Bogor Area, both partially and simultaneously. This can be seen from the results of data processing carried out by researchers, namely that price affordability has a significance value of 0.0477 <0.05 and tcount <ttable where this dimension has no significant effect, then the suitability of price with product quality has a significance value of 0.051 <0.05 and tcount < ttable where this dimension has a significant effect, then price compatibility with benefits has a significance value of 0.042 <0.05 and tcount > ttable where this dimension has a significant effect, and price competitiveness has a significance value of 0.000 <0.05 and tcount> ttable where this dimension is significantly influential, then with an fcount value of 11.907 > ftable 3.94 with a significance value of f 0.000 <0.05 where this result shows that all Variable X Price Perceptions influence the Decision to Stay. Keywords: Perceived Price, Decision to Stay, Villa